Associação entre retinopatia diabética e pé diabético em pacientes de um Centro de Referência do estado do Ceará - Braga, Darling Kescia Araújo Peixoto (2023)
Diabetes mellitus (DM) is one of the biggest health problems worldwide. One of its most important microvascular complications is diabetic retinopathy (DR), a neurovascular alteration that can be considered as the main cause of visual impairment and blindness worldwide. Diabetic foot (PD) is among the most serious complications of DM, being the most common cause of hospitalization in this population, impairing their productivity and quality of life, in addition to resulting in considerable clinical and economic burden. A combination of DR and PD would affect these individuals more severely, considerably compromising many aspects of their lives and the health system. Objective: To verify the association between DR and PD in patients treated at a reference center in the state of Ceará. Materials and methods: Crosssectional, quantitative study carried out with patients diagnosed with DR in a reference center in the state of Ceará, located in the city of Fortaleza-Ceará. The period of realization was from August 2021 to March 2022. The analyzed medical records were from January 2020 to December 2020. The selection of medical records was carried out by simple random sampling. The sample was divided into two groups with DM, one formed by individuals with DR and another group without. Population characteristics were described by measures of central tendency and dispersion for continuous variables, and frequency and percentage for categorical variables. The distribution of variables was tested using the Shapiro-Wilk test. Associations between categorical variables were assessed using the X² test. Means of continuous variables were compared using the Mann-Whitney test and the correlation between groups using Spearman's correlation coefficient. Logistic regression models were built for multivariate analysis between the explanatory variables and the presence of DR. P<0,05 was considered statistically significant. All analyzes were performed using the Statistical Package for the Social Sciences version 20.0. Results: 520 medical records were analyzed. The variables age group, sedentary lifestyle, medications, retinal mapping, comorbidities, type of DM, time since DM diagnosis and blood pressure showed significant differences between patients without and with DR(p<0,05). In the biochemical profile between the groups, the values of glycated hemoglobin (HbA1c), total cholesterol (TC), hemoglobin (Hb) and creatinine (Cr) were significantly differen (p<0,05). After multivariate analysis and adjustments for all significant variables in the bivariate analysis, the following variables remained associated with DR: age group, sedentary lifestyle, PD, TC, Hb and Cr. DR was significantly related to PD (p<0,001). When comparing the glycemic, blood pressure and anthropometric profile according to the DR severity level, only the HbA1C values showed significant differences (p=0.040). The PD was correlated with the glycemic, blood pressure and anthropometric profile variables. When comparing the severity of DR with the types of DM, it was found that there was no significant difference. Conclusion: PD had a high incidence in patients with DR who are followed up at a referral center in the state of Ceará in 2020, with a significant association between these complications.